A meta‐analysis of transcarotid versus transfemoral transcatheter aortic valve replacement. Issue 4 (12th May 2021) - McGrath, Daniel P.; Kawabori, Masashi; Wessler, Benjamin; Chen, Frederick Y.; Zhan, Yong
Abstract: Background: Carotid access has shown promise as an excellent delivery route for transcatheter aortic valve replacement (TAVR). We aimed to compare outcomes of transcarotid (TC) and transfemoral (TF) TAVR by conducting a search and analysis of the best evidence in the literature to shed light on its safety and effectiveness. Methods: The PubMed/MEDLINE, Embase, and Cochrane library from inception to July 2020 were searched to identify articles reporting comparative data on TC versus TF approaches for TAVR. Patients' baseline characteristics and clinical outcomes were extracted from the articles and pooled for analysis. Results: Five studies, including a total of 2470 patients, were included in the study with 1859 patients in the TF group and 611 patients in the TC group. The TC group had higher prevalence of peripheral vascular disease, while the patients in the TF group was older. Meta‐analysis revealed that there was no significant differences between the two groups with regard to 30‐day mortality ( p = 0.09), stroke ( p = 0.28), new dialysis ( p = 0.58), major bleeding ( p = 0.69), or pacemaker implantation ( p = 0.44). The TF group had a higher incidence of vascular complications (3.9% vs. 2.3%; OR 2.22; 95% CI [1.13, 4.38]; p = 0.02). Conclusions: Compared with the TF approach, TC‐TAVR is associated with comparable procedural and clinical outcomes. Our analysis found a lower rate of vascular complication in TC access compared with TF access. This supports consideration of such an alternative access when there are concerns over the feasibility of TF access.